Bispecific immunotherapy based on antibodies, T-cell receptors, and aptamers: mechanisms of action, adverse effects, and future perspectives - Lopatnikova, Julia A.; Sennikov, Sergey V. (Frontiers in Immunology, 2025)
Over the past decade, bispecific immunotherapeutic platforms have progressed from laboratory prototypes to multicenter clinical trials, inaugurating a new trajectory for precision oncology. This review synthesizes original studies that address the design principles, mechanisms of action, therapeutic efficacy, and limitations of three principal classes of bispecific molecules: (i) IgG-like antibodies, (ii) modified T-cell-receptor-based constructs (TCR-like and ImmTAC), and (iii) bispecific aptamers. IgG formats—including blinatumomab, teclistamab, mosunetuzumab, and tarlatamab—achieve high objective-response rates in hematologic malignancies and are increasingly demonstrating clinical activity in solid tumors. TCR-based constructs broaden the repertoire of actionable targets by recognizing intracellular antigens presented on MHC molecules, as exemplified by the approval of tebentafusp for uveal melanoma. Aptameric molecules exhibit minimal immunogenicity, rapid tissue penetration, and considerable promise as carriers for therapeutic payloads. We provide an in-depth analysis of the signaling cascades activated during T- and NK-cell redirection, immune checkpoint blockade, and direct inhibition of oncogenic receptors. Comparative evaluation of completed and ongoing clinical studies highlights recurring challenges and adverse events associated with bispecific platforms, including cytokine-release syndrome, neurotoxicity, antigenic drift, limited infiltration of densely fibrotic solid tumors, and the emergence of anti-drug antibodies. Engineering solutions under development encompass protease-activatable “masked” constructs, step-up dosing regimens, enzymatic remodeling of the extracellular matrix, and local expression of engager molecules via oncolytic viruses or adeno-associated viral vectors. Special emphasis is placed on combinatorial strategies in which bispecific agents are paired with CAR-T or γδ-T cells, PD-(L)1 inhibitors, or oncolytic viruses, thereby enhancing effector-cell infiltration and curtailing resistance. The integrated evidence indicates that continued progress in bispecific immunotherapy will depend on the incorporation of predictive molecular biomarkers, dynamic monitoring of the evolving antigenic landscape, and the standardization of biomanufacturing processes. These advances are expected to accelerate the clinical deployment of next-generation, multipurpose bispecific constructs.